Effects of endogenous and exogenous dissolved organic matter on sorption behaviors of bisphenol A onto soils. (1st June 2021) - Mo, Limei; Wang, Qiaohui; Bi, Erping
Abstract: The transport of organic contaminants in groundwater might be greatly affected by coexistence of dissolved organic matter (DOM) from different sources. In this study, the effects of endogenous and exogenous DOMs (referred to as DOMen and DOMex, respectively) on sorption behavior of bisphenol A (BPA) onto two reference soils were investigated by batch experiments and microscopic characterization. The results showed that BPA sorption onto soils was dominated by soil organic matter content and affected by DOM properties. The effect of DOMen on BPA sorption was also related to the inorganic components of the two soils. The decrease of organic matter content reduced the sorption capacity of fluvo-aquic soil. However, because the content of available inorganic components in black soil was high, after removing DOMen, more inorganic sites were exposed to increase the sorption capacity. In addition, DOMen could form complexes with BPA in solution, thus the removal of DOMen promoted BPA sorption onto black soil. Under the experimental conditions, contribution of DOMex to the total sorption of BPA onto both soils was not more than 30%. Results of dialysis experiments and soil sorption experiments indicated that effects of coexisting DOMex on BPA sorption was related to the affinity of DOMex to soils and complexation of BPA and DOMex . Since the affinity of DOMex to fluvo-aquic soil was relatively low, the complex of BPA and DOMex in solution was the main inhibition mechanism for BPA sorption. For black soil, higher complexation proportion of BPA with DOMex adsorbed onto soil which promoted BPA sorption onto soil. The findings are of significance for understanding the co-migration of DOM with BPA through soils. Graphical abstract: Image 1 Highlights: Removal of endogenous DOM could expose available inorganic sorption sites on soil. Distribution of exogenous DOM-BPA complexes determined BPA sorption to soils. Affinity between exogenous DOM and soil was the main factor affecting BPA sorption. Complexation of BPA to DOMex in solution inhibited sorption onto fluvo-aquic soil. DOMex sorbed onto black soil, and promoted co-sorption of BPA.